Downregulation of glutamic acid decarboxylase in Drosophila TDP-43-null brains provokes paralysis by affecting the organization of the neuromuscular synapses. - Romano, G.; Holodkov, N.; Klima, R.; Grilli, F.; Guarnaccia, C.; Nizzardo, M.; Rizzo, F.; Garcia, R.; Feiguin, F. (Scientific reports, 2018)
Amyotrophic lateral sclerosis is a progressive neurodegenerative disease that affects the motor system, comprised of motoneurons and associated glia. Accordingly, neuronal or glial defects in TDP-43 function provoke paralysis due to the degeneration of the neuromuscular synapses in Drosophila. To identify the responsible molecules and mechanisms, we performed a genome wide proteomic analysis to determine differences in protein expression between wild-type and TDP-43-minus fly heads. The data established that mutant insects presented reduced levels of the enzyme glutamic acid decarboxylase (Gad1) and increased concentrations of extracellular glutamate. Genetic rescue of Gad1 activity in neurons or glia was sufficient to recuperate flies locomotion, synaptic organization and glutamate levels. Analogous recovery was obtained by treating TDP-43-null flies with glutamate receptor antagonists demonstrating that Gad1 promotes synapses formation and prevents excitotoxicity. Similar suppression of TDP-43 provoked the downregulation of GAD67, the Gad1 homolog protein in human neuroblastoma cell lines and analogous modifications were observed in iPSC-derived motoneurons from patients carrying mutations in TDP-43, uncovering conserved pathological mechanisms behind the disease.